IN VITRO ANTI DERMATOPHYTE ACTIVITIES OF CRUDE METHANOL AND AQUEOUS EXTRACTS OF LAWSONIA INERMIS (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study was carried out to investigate the in vitro anti dermatophyte activities of crude methanol and aqueous extracts of Lawsonia inermis leaves. The anti dermatophyte activities was tested against Microsporum audouinii, Microsporum ferrugineum, Trichophyton megninii, Trichophyton tonsurans and Trichophyton rubrum, recovered from rice farmers with fungal skin infections in Anambra State, Nigeria. From the result obtained, growth of dermatophytes was inhibited at the varied concentrations of crude methanol extract with the diameter zone of inhibition increasing with the increase in concentration. At the lowest concentration of 10 mg/disc, diameter zone of inhibition range of 8.0 mm-16.8 mm was recorded against the different dermatophytes. At 80 mg/disc, T. rubrum showed the highest diameter zone of inhibition (18.8 mm), followed by M. audouinii (18.0 mm) while T. megninii was the least inhibited (12.0 mm). Water extract of L. inermis also inhibited all the test dermatophyte. M. audouinii was the most susceptible with diameter inhibition zone of 14.5 mm. Minimum inhibitory concentration was recorded at 25 mg/ml for all dermatophytes while fungicidal action was recorded at concentrations of 50 mg/ml for M. audouinii and T. rubrum, 100 mg/ml for M. ferrugineum and 200 mg/ml for T. megninii and T. tonsurans. These results demonstrated that L. inermis has anti dermatophyte activities and could be a good source for the production of plant based antifungal drugs.